A trend analysis of people living with human immunodeficiency virus attending an anti-retroviral therapy centre in urban Bangalore - N. R., Ramesh Masthi; Bharathi G., Divya; S., Pruthvi (International Journal Of Community Medicine And Public Health, 2021)
Background: HIV infection in India is a major public health problem. The anti-retroviral therapy (ART) centre is the backbone of the national acquired immune deficiency syndrome (AIDS) control program (NACO). To assess the trend of new people living with human immunodeficiency virus (PLHIV) registered at an ART centre in Bangalore and their treatment status. Methods: All the PLHIV registered at an ART centre from 1st January, 2009 to 31st December, 2018 were included in the study. PLHIV registered but not initiated on treatment, were excluded. Results: Out of 4428 PLHIV registered at an ART centre, 2964 were initiated on treatment. The youngest PLHIV registered was 6 years, oldest was 79 years and the decadal median age was 38 years. Majority (41.4%) were in the age group of 31 to 40 years. Predominant gender was male. A declining trend of new PLHIV, LFU/stopped/missed cases over the past decade was observed. The 1658 are alive, 402 died, 305 cases either missed, stopped or lost to follow up, 32 cases were opted out of the treatment and 567 cases were transferred out. Conclusions: A decline in number of new PLHIV, LFU, missed and stopped over the decade was observed.